Influenza polymerase activity correlates with the strength of interaction between nucleoprotein and PB2 through the host-specific residue K/E627. - Ng, A; Chan, W; Choi, S; Lam, M; Lau, K; Chan, P; Au, S; Fodor, E; Shaw, P (2012)
The ribonucleoprotein (RNP) complex is the essential transcription-replication machinery of the influenza virus. It is composed of the trimeric polymerase (PA, PB1 and PB2), nucleoprotein (NP) and RNA. Elucidating the molecular mechanisms of RNP assembly is central to our understanding of the control of viral transcription and replication and the dependence of these processes on the host cell. In this report, we show, by RNP reconstitution assays and co-immunoprecipitation, that the interaction between NP and polymerase is crucial for the function of the RNP. The functional association of NP and polymerase involves the C-terminal '627' domain of PB2 and it requires NP arginine-150 and either lysine-627 or arginine-630 of PB2. Using surface plasmon resonance, we demonstrate that the interaction between NP and PB2 takes place without the involvement of RNA. At 33, 37 and 41°C in mammalian cells, more positive charges at aa. 627 and 630 of PB2 lead to stronger NP-polymerase interaction, which directly correlates with the higher RNP activity. In conclusion, our study provides new information on the NP-PB2 interaction and shows that the strength of NP-polymerase interaction and the resulting RNP activity are promoted by the positive charges at aa. 627 and 630 of PB2.